Museum Education, Contemporary Architecture and Teenagers. A Step Towards the Shaping of Identity. Two Case Studies from MAXXI Education Department - Marta Morelli (Universidad Autónoma de Madrid, 2017)
The article examines the educational role of museums -particularly regarding informal architecture education- from a singular perspective, the one of MAXXI-National Museum of the 21st Century Arts. It's the first national museum devoted to contemporary art and architecture in Italy and promotes architecture education since its Education Department was set up. Starting from theoretical premises - the work of Eilean Hooper Greenhill above all - the article offers an overview of maxxi and presents two case studies relating to architecture learning projects devoted to teenagers "re-cycle. Experimental recycling workshop" and "Let me explain you contemporary architecture!" Stressing how museum education can influence the shaping of identity. Keywords: Museum, Education, Learning, School, Art.   Educación de Museos, Arquitectura Contemporánea y Adolescentes. Un paso hacia la Configuración de la Identidad. Dos Estudios de Caso del Departamento de Educación MAXXI El artículo examina el papel educativo de los museos -particularmente en lo que respecta a la educación informal de la arquitectura- desde una perspectiva singular, la del maxxi-Museo Nacional de las Artes del Siglo xxi. Es el primer museo nacional dedicado al arte contemporáneo y la arquitectura en Italia y promueve la educación arquitectónica desde la creación de su Departamento de Educación. Partiendo de las premisas teóricas -el trabajo de Eilean Hooper Greenhill sobre todo- el artículo ofrece una visión general de MAXXI y presenta dos estudios de caso relacionados con proyectos de aprendizaje de arquitectura dedicados a los adolescentes "re-cycle. Experimental recycling workshop" y "Let me explain you contemporary architecture!" Enfatizando cómo la educación museística puede influir en la formación de la identidad. Descriptores: Museo, Educación, Aprender, Escuela, Arte.   Educação em Museus, Arquitetura Contemporânea e Adolescentes. Um Passo para a Formação da Identidade. Dois Estudos de Caso do Departamento de Educação da MAXXI O artigo examina o papel educativo dos museus -sobretudo no que diz respeito à educação informal em arquitetura- a partir de uma perspectiva singular, a de MAXXI-Museu Nacional do Século xxi. É o primeiro museu nacional dedicado à arte contemporânea e arquitetura em Itália e promove a educação em arquitetura desde a criação do seu Departamento de Educação. A partir de premissas teóricas -o trabalho de Eilean Hooper Greenhill acima de tudo- o artigo oferece uma visão geral do maxxi e apresenta dois estudos de casos relativos a projetos de aprendizagem de arquitetura dedicados a adolescentes "re-cycle Experimental recycling workshop" e "Let me explain you contemporary architecture!" enfatizando como a educação nos museus pode influenciar a formação da uma identidade. Palavras-chave: Museu, Educação, Aprender, Escola, Arte.